STATUS EGO ANAK PADA PESERTA DIDIK DI SMA ISLAM BAWARI TAHUN 2021 - Nasywa, Mahdiyyah Rana (Jurnal Kajian Pembelajaran dan Keilmuan, 2022)
The purpose of this research is to know and describe the child's ego in students of SMA Islam Bawari Pontianak. The child's ego is an action or treatment based on a spontaneous emotional reaction. Besides that there are also reactive, humorous, creative and initiative traits. The subjects in this study were three students. This research uses a qualitative approach with a descriptive method and the form of the research is an intrinsic case study. Data collection techniques used are in-depth interviews, observations and home visits. Data analysis used an interactive model consisting of data reduction, data presentation and conclusion drawing. This research is reviewed in depth using a transactional analysis approach. Based on the results of the study, the characteristics of the child's ego. The ego status of the conforming child is submissive, manipulated, spoiled, the natural child's ego status is spontaneous, rebellious, curious, and creative. The factors that cause students to study about the child's ego are (1) family, (2) ethics or culture, (3) loneliness. The impact the child's ego status includes the school environment, friendships, how to solve a problem. The role of the counseling guidance teacher is to monitor the development of students by collaborating with field teachers, homeroom teachers and parents.